Exploring the Beauty of the Banjarmasin River through 3D Animation as a Visual Tourism Media - Nisa, Zapiratun; Adriani, Adella; Pepriyani, Nor Lintang; Sabrila, Trifebi Shina (INSTALL: Information System and Technology Journal, 2025)
The city of Banjarmasin is known as the "City of a Thousand Rivers," which has enormous tourism potential, especially in terms of unique river tourism. However, the public's interest, especially the younger generation, in river tourism began to decline due to the lack of interesting and informative promotional media. This research aims to create 3D animation as a means of visualization to promote river tourism in Banjarmasin with a Research and Development (R&D) approach. The development process consists of three main stages: pre-production, production, and post-production, which is carried out using Blender software. The results of the animation show community activities along the Martapura River, which includes floating markets, kelotok boats, and traditional atmosphere on the riverbank. These animations were created based on observational data and field records to reflect the local culture in an authentic way. The findings of the study indicate that 3D animation functions well as an attractive and informative visual promotional tool, and has the potential to increase tourist interest in tourist destinations in Banjarmasin through digital platforms.